PENGARUH RISIKO KREDIT DAN TINGKAT KECUKUPAN MODAL TERHADAP TINGKAT PROFITABILITAS PADA BAITUL MAAL WAT TAMWIL (BMT) PRINGSEWU - Reny, Armalia (Media Mahardhika, 2020)
This research purposed to test wheter or not there is the effect of credit risk as measured by the ratio of  Non Performing Financings (NPF) and Capital Adequacy as measured using the Capital Adequacy Ratio (CAR) to the level of profitability as measured using the ratio of Return On Equity (ROE) on Baitul Maal wat Tamwil (BMT) Pringsewu.Population in this research that the Baitul Maal wat Tamwil Pringsewu. As a sample of financial statement BMT Pringsewu for five years from 2010 until 2014. The analutical method used is multiple regression analysis. Based on the result of  multiple regression analysis with significance level of 5% or 0.05 , then the result of this research can be concluded that (1) simultaneous independent variables that affect the NPF and CAR to ROE (2) NPF has a negative influence on the ROE while (3) CAR positive effect on ROE..